Urgensi Reformasi Hukum Pidana Hak Cipta terhadap Pembajakan Sinematografi di Media Sosial TikTok Indonesia Digital - Oesman Bahari Abdullah; O.K. Saidin; Putri Rumondang Siagian (Mahesa Research Center, 2026)
Cinematographic piracy on TikTok presents a significant challenge to the enforcement of criminal copyright law in Indonesia. The platform’s short-video format, viral nature, and monetization potential have facilitated the widespread distribution of unauthorized film excerpts. Although Law Number 28 of 2014 on Copyright provides criminal sanctions for copyright infringement, its enforcement remains ineffective, primarily due to the classification of copyright offenses as complaint-based crimes. This study aims to examine the regulation of criminal copyright law in addressing film piracy on TikTok and to analyze the urgency of reforming the offense classification and adopting more adaptive criminal sanctions. This research employs a normative legal method with a juridical-normative approach, relying on statutory analysis, legal doctrines, and relevant scholarly literature. The findings indicate that the complaint-based offense mechanism and non-proportional sanctions relative to the perpetrators’ economic gains undermine deterrence and weaken copyright protection. Therefore, legal reform is necessary through the adoption of a mixed offense model based on the perpetrator’s characteristics and the implementation of adaptive sanctions to enhance the effectiveness of copyright law enforcement in the digital era.